2012 11th International Conference on Environment and Electrical Engineering 2012
DOI: 10.1109/eeeic.2012.6221472
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic based DC bus voltage control of a stand alone photovoltaic/fuel cell/supercapacitor power plant

Abstract: A renewable energy hybrid power plant, fed by photovoltaic (PV) and fuel cell (FC) sources with a supercapacitor (SC) storage device and suitable for distributed generation applications, is proposed herein. The PV is used as the primary source; the FC acts as a backup and a long-term storage system, feeding only the insufficiency power (steady-state) from the PV; and the SC functions as an auxiliary source and a shortterm storage system for supplying the deficiency power (transient and steady-state) from the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thounthong et al [38]designed a mathematical model of hybrid PV/FC/SC. A dynamic optimization is proposed using intelligent fuzzy logic controller.…”
Section: Supercapacitormentioning
confidence: 99%
See 1 more Smart Citation
“…Thounthong et al [38]designed a mathematical model of hybrid PV/FC/SC. A dynamic optimization is proposed using intelligent fuzzy logic controller.…”
Section: Supercapacitormentioning
confidence: 99%
“…A dynamic optimization is proposed using intelligent fuzzy logic controller. Several others proposed the same system with the energy management approach [38,39] Various configurations have been proposed by previous studies which can be concluded that they can be classified in term of energy storage method. In the early stage a simple system which only consisting of battery is used.…”
Section: Supercapacitormentioning
confidence: 99%
“…Beyond finding new alternative fuels and methods, the hybrid power configuration is commonly accepted to solve the current problems. The hybrid power systems one can use fossil fuels combined with electric power storage such as battery or super capacitors to promote the efficiency, the other can use fuel cells, solar cells combined with electric power storages to form a zero-emissions power system with a long lasting operation or low-cost consumption strategies [1][2] [4][5] [6] [13][14] [16].…”
Section: Introductionmentioning
confidence: 99%